Heterogeneity of CD34 and CD38 expression in acute B lymphoblastic leukemia cells is reversible and not hierarchically organized. Issue 1 (December 2016) - Jiang, Zhiwu; Deng, Manman; Wei, Xinru; Ye, Wei; Xiao, Yiren; Lin, Simiao; Wang, Suna; Li, Baiheng; Liu, Xin; Zhang, Gong; Lai, Peilong; Weng, Jianyu; et al.
Abstract The existence and identification of leukemia-initiating cells in adult acute B lymphoblastic leukemia (B-ALL) remain controversial. We examined whether adult B-ALL is hierarchically organized into phenotypically distinct subpopulations of leukemogenic and non-leukemogenic cells or whether most B-ALL cells retain leukemogenic capacity, irrespective of their immunophenotype profiles. Our results suggest that adult B-ALL follows the stochastic stem cell model and that the expression of CD34 and CD38 in B-ALL is reversibly and not hierarchically organized.